2018
DOI: 10.1021/acsphotonics.7b01346
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of Plasmonic Materials in the Visible and Near-Infrared: Linear, Refractory, and Nonlinear Optical Properties

Abstract: Plasmonic nanostructures are used today for a variety of applications. Choosing the best suited plasmonic material for a specific application depends on several criteria, such as chemical and thermal stability, bulk plasma frequency, nonlinear response, and fabrication constraints. To provide a comprehensive summary, we compare these properties for eight different plasmonic materials, namely, Ag, Al, Au, Cu, Mg, Ni, Pd, and Pt. All these materials can be fabricated with electron beam lithography and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 51 publications
2
48
0
Order By: Relevance
“…Recently, there has been an increasing interests in NLO properties of metallic nanoparticles (NPs), which have proved to be highly valuable for a variety of applications including plasmon-enhanced spectroscopies, biosensing, optical tweezers, optical bistability, ultrafast optical switch and modulation, optoelectronic devices, and so on [1][2][3][4][5][6][7]. The NLO responses of metallic NPs are in a large extent determined by the plasmonic resonances (surface plasmon resonance (SPR) for extended metallic surfaces, and localized surface plasmon resonance (LSPR) for metallic NPs), which are the conduction electron coherent oscillations stimulated by the incident light and strongly dependent on NPs' geometry and surroundings [1,[8][9][10][11][12][13]. Therefore, it provides a great platform for modulating the optical responses by tuning the metallic NPs' shapes, sizes, and environments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increasing interests in NLO properties of metallic nanoparticles (NPs), which have proved to be highly valuable for a variety of applications including plasmon-enhanced spectroscopies, biosensing, optical tweezers, optical bistability, ultrafast optical switch and modulation, optoelectronic devices, and so on [1][2][3][4][5][6][7]. The NLO responses of metallic NPs are in a large extent determined by the plasmonic resonances (surface plasmon resonance (SPR) for extended metallic surfaces, and localized surface plasmon resonance (LSPR) for metallic NPs), which are the conduction electron coherent oscillations stimulated by the incident light and strongly dependent on NPs' geometry and surroundings [1,[8][9][10][11][12][13]. Therefore, it provides a great platform for modulating the optical responses by tuning the metallic NPs' shapes, sizes, and environments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential source of errors is nanoantenna damage owing to overheating, which might change its optical properties. However, a recent study 31 has shown that coating of plasmonic nanoantennas with a protective Al 2 O 3 thin layer gives rise to unchanged both linear and nonlinear responses during 10-min illumination at a pulse repetition rate of 44 MHz and a pulse intensity 0.6 GW cm −2 . This observation allows us to believe that this issue is also avoidable.…”
Section: Discussionmentioning
confidence: 99%
“…28 Alteration of the structural symmetry of nanoparticles can inuence their linear optical, non-linear optical, electronic, catalytic and even biological properties. [29][30][31][32][33][34] Anisotropic metallic nano particles possess asymmetry axes, and this break in symmetry leads to remarkable optical and chemical properties. Although there have been a large number reports on various anisotropic systems, hydrogen peroxide together with trisodium citrate mediated green synthesis, nonlinear optical and photo catalytic analysis of anisotropic silver nano prisms have seldom been studied.…”
Section: Introductionmentioning
confidence: 99%